Implementation Of Pursed Lip Breathing And Semi Fowler Position in COPD Patients Which Get Nebulizer in IGD: A Literature Review - Ariefkhoerulummah Nurgiyanta; Galih Noor Alivian (Journal of Bionursing, 2020)
Background: Chronic obstruction of pulmonary disease (COPD) is a pulmonary disease caused by the blockage of the air flow channel that occurs much in Indonesia due to the high exposure to the risk factors causing COPD such as the habit of smoking and unhealthy environment. The obstruction of the respiratory tract that occurs in COPD patients is usually characterized by shortness of breath. Various ways can be done to overcome shortness of breath is with pharmacological therapy in the form of nebulizer therapy. One of the effective non-pharmacological therapies to reduce shortness of breath with pursed lip breathing therapy and the giving of semi Fowler position. Objectives: Identify the research articles that display the results of analysis of the introduction of pursed lip breathing and the provision of semi Fowler in COPD patients who get therapy nebulizer in IGD space Research Method: The search for articles is done electronically using a Sience Direct, NCBI and Google Scholar databases. The search for the article used is the last 5 years. Keyword in search "pursed lip breathing, position semi-Fowler and chronic obstructive pulmonary disease" so obtained 5 research articles in review. Results: The feeding of pursed lip breathing and the giving of semi Fowler can effectively lower the shortness of breath in COPD patients. Step in the intervention of this combination by encouraging the patient to inhale the breath from the nose and the patient bent forward 30 to 40 degrees with the head lifted 16 to 18 degrees breathed slowly through the lips as much as 7 counts later afterwards the patient positions the Head 45 Conclusion: The feeding of pursed lip breathing and the giving of semi Fowler is proven to decrease the shortness of breath in COPD patients Keyword: pursed lip breathing, position semi-fowler dan chronic obstructive pulmonary disease